Viability testing and transplantation of marginal livers (VITTAL) using normothermic machine perfusion: study protocol for an open-label, non-randomised, prospective, single-arm trial. Issue 11 (28th November 2017) - Laing, Richard W; Mergental, Hynek; Yap, Christina; Kirkham, Amanda; Whilku, Manpreet; Barton, Darren; Curbishley, Stuart; Boteon, Yuri L; Neil, Desley A; Hübscher, Stefan G; Perera, M Thamara P R; Muiesan, Paolo; et al.
Abstract : Introduction: The use of marginal or extended criteria donor livers is increasing. These organs carry a greater risk of initial dysfunction and early failure, as well as inferior long-term outcomes. As such, many are rejected due to a perceived risk of use and use varies widely between centres. Ex situ normothermic machine perfusion of the liver (NMP-L) may enable the safe transplantation of organs that meet defined objective criteria denoting their high-risk status and are currently being declined for use by all the UK transplant centres. Methods and analysis: Viability testing and transplantation of marginal livers is an open-label, non-randomised, prospective, single-arm trial designed to determine whether currently unused donor livers can be salvaged and safely transplanted with equivalent outcomes in terms of patient survival. The procured rejected livers must meet predefined criteria that objectively denote their marginal condition. The liver is subjected to NMP-L following a period of static cold storage. Organs metabolising lactate to ≤2.5 mmol/L within 4 hours of the perfusion commencing in combination with two or more of the following parameters—bile production, metabolism of glucose, a hepatic arterial flow rate ≥150 mL/min and a portal venous flow rate ≥500 mL/min, a pH ≥7.30 and/or maintain a homogeneous perfusion—will be considered viable and transplanted into a suitable consented recipient. The coprimary outcome measures are the success rate of NMP-L to produce a transplantable organ and 90-day patient post-transplant survival. Ethics and dissemination: The protocol was approved by the National Research Ethics Service (London—Dulwich Research Ethics Committee, 16/LO/1056), the Medicines and Healthcare Products Regulatory Agency and is endorsed by the National Health Service Blood and Transplant Research, Innovation and Novel Technologies Advisory Group. The findings of this trial will be disseminated through national and international presentations and peer-reviewed publications. Trial registration number: NCT02740608; Pre-results .